PENGEMBANGAN TES HASIL BELAJAR HIGHER ORDER THINKING SKILL (HOTS) MATERI PERSAMAAN KUADRAT KELAS IX SMP - Herlina Sari Br Sitepu; Kana Hidayati (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This study aims to produce a set of HOTS-based mathematics learning outcomes tests on quadratic equations that are valid, reliable & effective. The instrument developed can measure the cognitive domain of students and is in the form of a description with 6 questions. This research is a development research with a formative evaluation type consisting of two stages namely; (1) preliminary includes self-evaluation & design and (2) prototyping includes expert review, one-to-one, small group and field test. The results of the research show that a learning achievement test has been successfully developed on the subject of quadratic equations which can measure the cognitive domain from the aspect of validity and effectiveness. Effectiveness can be seen from the completeness of student learning as much as 12.12% with an achievement indicator of 73% and a positive response of 87.4% and the learning time and tests carried out do not exceed the time provided. Based on the analysis of the HOTS questions on the quadratic equation material, an average value of 55 was obtained and showed that the level of high-level thinking skills in the student category was sufficient